Answer:
Standard form is Ax + By = C where A is a positive integer
3x+1 = 2y
-2y -2y
3x-2y +1 =0
-1 -1
3x - 2y = -1
Step-by-step explanation:
When multiplying two equations like this, you need to distribute. Distribute each term to get <span><span><span><span><span><span>3<span>x</span></span></span></span></span></span></span>
![x^{6}](https://tex.z-dn.net/?f=%20x%5E%7B6%7D%20)
<span><span><span><span><span>+ <span>3</span></span></span></span></span></span>
![x^{5}](https://tex.z-dn.net/?f=%20x%5E%7B5%7D%20)
<span><span><span><span>− <span>26</span></span></span></span></span>
![x^{4}](https://tex.z-dn.net/?f=%20x%5E%7B4%7D%20)
<span><span><span>−<span>14</span></span></span></span>
![x^{3}](https://tex.z-dn.net/?f=%20x%5E%7B3%7D%20)
<span><span>−<span>15</span></span></span>
![x^{2}](https://tex.z-dn.net/?f=%20x%5E%7B2%7D%20)
<span>−<span>24x</span></span>+<span>3</span>
For the answer to the question above,
z=6-(3/4)y-2x
<span>z+(3/4)y+2x=6 </span>
<span>Just by connecting the three points on the graph, I got this equation by isolating each plane to figure it out. This equation only explains the plane bounded by these three points, though, so to draw it just plot the points and connect them.</span>
<span><span>anonymous </span> 3 years ago</span>we are solving for A,
A is the future amount A=?
P is the present value, so we were told 7,900, so p=7900
r is the interest rate, so 4.3%, but in decimal form so r=0.043
k is the how often it is 'compounded', it says quarterly, so k=4
n is how long, 3 years, so n=3
<span>A=P(1+<span>rk</span><span>)<span>n∗k</span></span></span>
plug in the values
<span>A=8981.51</span>
Factor by grouping. Group up the terms into pairs, factor each pair, then factor out the overall GCF.
x^3 + 2x^2 - 16x - 32
(x^3 + 2x^2) + (-16x-32) ... pair up terms
x^2(x + 2) + (-16x - 32) ... factor x^2 from the first group
x^2(x + 2) - 16(x + 2) ... factor -16 from the second group
(x^2 - 16)(x + 2) .... factor out (x+2)
(x - 4)(x + 4)(x + 2) .... Use the difference of squares to factor x^2-16
---------------------------
The original expression completely factors to (x - 4)(x + 4)(x + 2)
The three factors are x - 4 and x + 4 and x + 2